Reassortant H5N1 Avian Influenza Virus Bearing PB2 Gene From a 2009 Pandemic H1N1 Exhibits Increased Pathogenicity in Mice - Lin, Xian; Yu, Shiman; Guo, Kelei; Sun, Xin; Yi, Haiming; Jin, Meilin (Frontiers in Microbiology, 2018)
Reassortment is a key driving force of the evolution and host adaptation of the influenza virus. A(H1N1)pdm2009 (pdm09), a novel H1N1 influenza viral subtype, caused a pandemic in 2009. The strain was established in pig herds and cocirculated with the highly pathogenic H5N1 avian influenza virus. The coexistence of pdm09 with H5N1 raises concerns that reassortment may cause the development of novel viral strains with unpredictable virulence. Given that the viral polymerase subunit PB2 is a determinant of host range and pathogenicity, and that the substantial amino acid differences in PB2 between pdm09 and H5N1, including positions 590/591 and 271, which are shown to play key roles in enhanced polymerase activity in mammalian host cells, we generated a reassortant virus containing PB2 derived from a pdm09 (A/Liaoning/1/2009, LN/09) to investigate if pdm09-derived PB2 can function in a heterologous avian virus isolate as an adaptive strategy, with H5N1 (A/duck/Hubei/hangmei01/2006, HM/06) as the backbone. We assessed the biological characteristics, including pathogenicity, replication, and polymerase activity, of the reassortant. Compared with HM/06 and LN/09, H5N1 hybrid virus containing PB2 from LN/09 exhibited significantly increased pathogenicity in mice and proliferation activity in mammalian cell lines, as well as markedly enhanced polymerase activity. Our results indicate that the coexistence of H5N1 and pdm09 may pose a great threat to public health through reassortment. Moreover, our results highlight the importance of monitoring the emergence of H5N1 reassortants containing pdm09-derived PB2.